(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: A community is a group of people living in the particular places having common religion, norms and value. It is a social group with geographical boundaries. Community Health Diagnosis (CHD) address the total well-being of a people occupying a particular place, eliminating health related disease. “CHD is a comprehensive assessment of the state of entire community in relation to its economic, social, physical, and biological environment”. It is a process of examining the pattern of disease in the community and describing it in terms of its importance factors mortality, morbidity, and fertility rate. CHD is use to determine the magnitude of community health related problem, fixing the health problem in priority order, running effective health intervention program and exploring the existing resources. Materials and Methods: The study was conducted by face-to-face interview among the 290 household of ward 2 of Bardibas Municipality, Mahottari district, Madhesh Province of Nepal, using semi-structured questionnaire with inclusion of community health parameters. The convenient sampling method was used for the study. Verbal informed consent was taken from the respondent as well as the local administrative office before commencing the study. The data was collected in the month of May-June 2017. Results: The result showed that the community health status of the study area was satisfactory but still there is huge gap between the needs, services and their utilization. Although maximum children are vaccinated according to expanded programme on immunization, most of the people used latrine for defecation, and almost resident use tap water for drinking. Conclusions: The various related stakeholders of the community should work efficiently to mitigate the gap between health problems and needs in the community. The health program should be specially planned, implemented and analyzed in the deprived and marginalized area of society to address the disparity in the social, economic and health needs.